Low Concentrations of Eucalyptus Essential Oil Induce Age, Sex, and Mating Status-Dependent Stimulatory Responses in Drosophila suzukii - Maria Pineda; Emanuel Lucas de Andrade Alves; Julia Almeida Antunes; Vinícius de Castro Carvalho; Khalid Haddi (Agriculture, 2023)
Plant-extracted essential oils are generally suggested as potential sources for alternatives to synthetic insecticides in insect pest control strategies. The increased interest in the use of essential oils derives from the generalized perception of their safety for the environment, human health, and non-target organisms as well as a lower risk of resistance development. However, studies on essential oils have largely focused on their activity on targeted insect pests while overlooking their potential unintended effects on insect biological and reproductive traits, especially with sublethal exposures. Here, we first determined the toxicity of Eucalyptus globulus essential oil to adults of Drosophila suzukii and assessed the effects of low concentrations (i.e., LC5 and LC20) in old (5–7 days) and mated flies. Subsequently, we assessed longevity and fecundity in newly emerged virgin flies from four couples’ combinations: unexposed couples, exposed females, exposed males, and exposed couples to the low concentration LC20. Our results show that eucalyptus essential oil has good insecticidal activity against adults of D. suzukii. However, compared to untreated flies, the exposure to low concentrations enhanced the females’ fecundity only when both old and mated female and male flies were exposed, while the females’ but not males’ life span was extended only in couples where newly emerged virgin females were exposed. Our findings suggest that although the eucalyptus essential oil may be a good control alternative for adult D. suzukii, its age-, sex-, and mating status-dependent stimulatory responses mediated by exposure to low concentrations need to be considered and further investigated.